Phytophthora capsici carries and differentially expresses genes for the RNA interference pathway - Jacobo Sevillano-Serrano; Fernando Uriel Rojas-Rojas; Alfonso Méndez-Bravo; Nancy Calderón-Cortés; Harumi Shimada-Beltrán; Julio Vega-Arreguín (PLoS ONE, 2026)
The RNA interference (RNAi) pathway is an epigenetic mechanism that has recently gained attention for its role in regulating the virulence of plant pathogens. However, little is known about this gene silencing pathway in Phytophthora capsici , a broad-host-range pathogen that affects many important food crops. In the present study, we identified key genes and proteins involved in the synthesis, transport, and processing of sRNAs using in silico approaches based on the reference genome and proteome, and through transcriptional analysis of P. capsici . Our results showed that the P. capsici genome encodes Dcl1, Dcl2, Exportin-5, Rdr, and six Ago proteins, suggesting the presence of a complete RNAi pathway in this pathogen. These genes were syntenic and phylogenetically related to those of other oomycetes in the genus Phytophthora . We also analyzed their expression levels after infecting chili pepper and broccoli across two generations, revealing different expression patterns depending on the infection history of the pathogen. To our knowledge, this is the first report on the EXPORTIN-5 gene in P. capsici and other oomycetes. Additionally, the expression of all these RNAi-related genes in the pathogen after isolation from different hosts suggests that the host may influence the RNAi pathway of P. capsici . This study paves the way for functional studies to confirm the role of RNAi in regulating virulence in P. capsici .